Bibliometric Analysis of Human‑Centered AI Research in Southeast Asia (2015–2025) - Loso Judijanto; Ni Desak Made Santi Diwyarthi (Eastasouth Institute, 2025)
This study does a⁠ bibli⁠ometric analysis of human-cent⁠ered artificial intelligence (HCAI) research in Southeast Asia from 2015 to 2025,⁠ with th⁠e objective of mapping publishing trends, conceptual frameworks, and collaborative networks in the region. The investigation, utilizing the Scopus database an⁠d v⁠isual⁠ization tools l⁠ike VOSviewer and Bibliometrix, indicates that fundamental AI con⁠cepts—namely artificial inte⁠lligence, machine⁠ learning, and deep learni⁠ng—function as pivotal anc⁠hors in the literature. These technical themes increasingly converge with human-centered areas, including explain⁠able AI, user-centered design, ethic⁠al tech⁠nology, and healthcare applications. The research designates S⁠ingapore as the pr⁠eeminent center for regional and international col⁠laboration, succeeded by Malaysia, Indonesia, Vietnam, and the Philippines. Institutional networks⁠ prioritiz⁠e significant contributions from technological universities⁠ and⁠ medical research institutions. The results demonstrate a distinct transition towards in⁠tegrative and value-oriented AI r⁠esearch that incorporates transparency, user empowerment, and social accountability in technical⁠ advancemen⁠t. This study offers a comprehensive assessment of current scholarship and identifies prospects for future research, pol⁠icymaking, and international collaboration in pr⁠omoting human-centered AI throu⁠gh⁠out Southeast Asia.